«Союз українок» у таборах інтернованих вояків Армії УНР в Польщі (1921-1922 рр.): основні напрями діяльності - Ihor Sribnyak; Maryna Paliienko (Facta Simonidis, 2021)
The article discusses the main activities of the units of the Union of Ukrainian Women in the internment camps for the UPR Army soldiers in Poland in the years 1921-1922. Most importantly, the members of the union nursed sick and disabled Ukrainian soldiers, as well as women and children. Thanks to their efforts, the living conditions of the most vulnerable camp residents (in particular, children, including infants and toddlers) were improved. For example, the Union of Ukrainian Women ensured a minimum nutrition supply for that group along with daycare in special institutions established by the union. All of this was possible thanks to the support of charity organizations, which spared no expense, always coming to the aid of women and children who permanently resided in the camps.